KARAKTERISTIK FISIKOKIMIA DAN SENSORI SNACK BAR AMPAS TAHU DENGAN PENAMBAHAN KACANG BOGOR - Purnama, Hilman; Hutami, Rosy; Novidahlia, Noli (Jurnal Ilmiah Pangan Halal, 2019)
Snack bar is solid food that shaped bar and is a mixture of various dry materials as cereal, nuts, fruits, combined into one with the binders assistance. This study aims to diversify fiber rich food waste based tofu dregs and bambara groundnut. This study uses a Completely Ramdomized Design (CRD) factorial with two factors methods and Completely Ramdomized Design (CRD) of one factors menthods. This study consisted of three stages of that make flour tofu dregs, temperature determination and roasting time and formulation snack bar. Testing used are hardness test used a texture analyzer, hedonic and sensory quality test which  attributes  are  flavor, color,  odor and hardness. Furthemore chemical test (moisture content, ash content, carbohydrates, protein, fat) and the dietary fibers  also used on  the selected sample  only. Analysis of the data used is  Analysis Of Variance (ANOVA) with a duncan  further test. Snack bar with temperature and time is snack bar with hardness of 1183.33 gf. The  results  of  chemical test shows that C3 snack bar has 57,18% of carbohydrates, 14.40% of protein, 15,69 fat, 11,62% of water content, 1,1% of ash content, 427 Kcal of calories, and dietary fibers 10,34%.